2021
DOI: 10.1109/access.2021.3051023
|View full text |Cite
|
Sign up to set email alerts
|

Making the Sourcing Decision of Software Maintenance and Information Technology

Abstract: Outsourcing has been getting a significant growth for the last few years. Organizations tend to outsource Information Technology (IT), primarily to take advantage of the availability of qualified, trained and skilled workforce in low cost countries across the globe. Outsourcing of IT and software maintenance seem very promising, but a number of factors, risks, and challenges associated with the outsourcing process that make the sourcing decision very complicated. The present study aimed at gaining in-depth und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 79 publications
0
18
0
1
Order By: Relevance
“…The influencing factors were further evaluated in the outsourcing industry by performing an empirical study [1] that ranked 10 factors as critical success factors. In the current study, a MCDM model is developed based on the influencing factors identified in [2,3], and which were further validated and reported in [1]. Literature review showed that previous studies [5,24,28,30,38,39] also adopted the same method.…”
Section: Proposed Methodsmentioning
confidence: 96%
See 4 more Smart Citations
“…The influencing factors were further evaluated in the outsourcing industry by performing an empirical study [1] that ranked 10 factors as critical success factors. In the current study, a MCDM model is developed based on the influencing factors identified in [2,3], and which were further validated and reported in [1]. Literature review showed that previous studies [5,24,28,30,38,39] also adopted the same method.…”
Section: Proposed Methodsmentioning
confidence: 96%
“…To achieve our target, the existing literature was thoroughly analyzed by performing two systematic literature reviews that identified influencing factors of application maintenance offshoring. The conducted systematic literature reviews are cited as [2,3] that give a list of influencing factors regarding offshoring the application maintenance.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 3 more Smart Citations